Cleistochlamys kirkii chemical constituents: Antibacterial activity and synergistic effects against resistant Staphylococcus aureus strains. (3rd February 2016) - Pereira, Filipe; Madureira, Ana Margarida; Sancha, Shirley; Mulhovo, Silva; Luo, Xuan; Duarte, Aida; Ferreira, Maria-José U.
Abstract: Ethnopharmacological relevance: Cleistochlamys kirkii (Benth) Oliv., (Annonaceae) is a medicinal plant traditionally used in Mozambique to treat infectious diseases. Aims of the study: To find antibacterial lead compounds from C. kirkii and provide scientific validation for its use in traditional medicine. Materials and methods: Through bioassay-guided fractionation, nine compounds (1–9 ), with different scaffolds, were isolated from the methanol extract of C. kirkii whose structures were identified by spectroscopic methods. Compounds1–9 were evaluated for their in vitro antibacterial activity against a panel of eight Gram-positive, including five drug-resistant strains of Staphylococcus aureus, vancomycin-resistant Enterococcus faecalis, and two Gram-negative bacteria strains. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined. A chemosensitization assay, using the checkerboard method, was also performed in order to evaluate the type of interaction of compounds with antibiotics/compounds against two S. aureus resistant strains (ATCC 9144 and CIP 106760) and a susceptible strain (ATCC 6538). Results: Dichamanetin (3 ), a rare C -benzylated flavanone, was very active against all the Gram-positive strains tested, displaying MIC values in the range of 1–7.5 μg/mL. The C -benzylated flavanones chamanetin (1 ), isochamanetin (2 ), and the α, β-unsaturated lactone (−)-cleistenolide (6 ) also showed relevant antibacterial activity against some of the Gram-positive strains assayed. Compounds4, 5, and7–9 have shown no significant activity at the concentration ranges tested. In the combination with antibiotics, polycarpol (8 ) (MIC 125 μg/mL) showed a strong synergistic effect against the methicillin-resistant S. aureus ATCC 9144. When combined with oxacillin (MIC 125 μg/mL), compound8 reduced the MIC to 1.5 μg/mL (FICI=0.11). Similarly, it reduced the MIC of amoxicillin (MIC 250 μg/mL) to 7.5 μg/mL (FICI=0.18). Synergy was also obtained when this compound was combined with both β -lactam antibiotics (FICI=0.30) and with vancomycin (FICI=0.24) against vancomycin-intermediate S. aureus (VISA) CIP 106760. Remarkable, compound8 was also able to reduce synergistically the MIC value of dichamanetin (3 ) (FICI=0.18) against this strain. Conclusions: These results suggested that C. kirkii constituents may be valuable as a leads for restoring antibiotic activity against resistant S. aureus strains. Graphical abstract: